Advancing Sustainable Higher Education: Embracing the Triple Bottom Line Integration in Uganda - Gichuru, Eutychus Ngotho (East African Journal of Education Studies, 2024)
The purpose of this conceptual paper was to revise Triple Bottom Line Theory of sustainable development as proposed by John Elkington, so as to propose ways of advancing sustainable higher education in Uganda. The major tenets of this theory are economic viability, environmental sustainability and social responsibility. Reduced fiscal spending by governments to higher education, the global calls for mitigation of climate change, youth unemployment and equity calls for higher education to be sustainable, including in Uganda. This paper concludes by proposing that sustainable higher education in Uganda is as a result of : Economic viability (job creation, skill development, research & innovation, community engagement, global education- partnerships with international institutions), environmental sustainability (integration of sustainability in curricula, use of experiential learning, collaboration with stakeholders, addressing resource limitations, empowerment and economic benefits) and social responsibility (community engagement, addressing local and global challenges, integrating social responsibility into missions, and merging social responsibility with internationalization efforts). The paper concludes by recommending empirical validation of the model, both in Uganda and outside Uganda